Accuracy of Doppler blood pressure measurement in continuous‐flow left ventricular assist device patients. (17th May 2019) - Li, Song; Beckman, Jennifer A.; Welch, Nathan G.; Bjelkengren, Jason; Masri, Sofia Carolina; Minami, Elina; Stempien‐Otero, April; Levy, Wayne C.; O'Brien, Kevin D.; Lin, Shin; Farris, Stephen D.; Cheng, Richard K.; et al.
Abstract: Aims: Accurate blood pressure (BP) measurement in continuous‐flow ventricular assist device (CF‐VAD) patients is imperative to reduce stroke risk. This study assesses the accuracy of the Doppler opening pressure method compared with the gold standard arterial line method in CF‐VAD patients. Methods and results: In a longitudinal cohort of HeartMate II and HVAD patients, arterial line BP and simultaneously measured Doppler opening pressure were obtained. Overall correlation, agreement between Doppler opening pressure and arterial line mean vs. systolic pressure, and the effect of arterial pulsatility on the accuracy of Doppler opening pressure were analysed. A total of 1933 pairs of Doppler opening pressure and arterial line pressure readings within 1 min of each other were identified in 154 patients (20% women, mean age 55 ± 15, 50% HeartMate II and 50% HVAD). Doppler opening pressure had good correlation with invasive mean arterial pressure ( r = 0.742, P < 0.0001) and more closely approximated mean than systolic BP (mean error 2.4 vs. −8.4 mmHg). Arterial pulsatility did not have a clinically significant effect on the accuracy of the Doppler opening pressure method. Conclusions: Doppler opening pressure should be the standard non‐invasive method of BP measurement in CF‐VAD patients.